Factors Affecting Labor Productivity of Palm Oil Harvesters at PT. Betami, Rantau District, Aceh Tamiang Regency - Muhammad Ichsan Maulana (Journal of Accounting Research, Utility Finance and Digital Assets, 2022)
Muhammad Ichsan Maulana (2022). The purpose of this study was to analyze the effect of age, work experience, number of dependents, salary of supporting facilities and motivation on work productivity of oil palm harvesters at PT, Betami Kebun Rantau, Aceh Tamiang Regency. The analytical method used is multiple linear regression analysis with SPSS 24.0 tool. The sampling method used the census method and the sample of this study amounted to 35 employees of oil palm harvesters at PT. Betami Overseas Gardens, Aceh Tamiang Regency. Determination of the research area is done purposively. The results of the study concluded that the work productivity of oil palm harvesters was high, i.e. 50,000 – 52,000 Kg/HKP/Month. Factors Age, Work Experience, Number of Dependents, and Motivation have no significant effect on the work productivity of oil palm harvesting employees at PT. Betami Rantau Farms while the Salary and Supporting Facilities have a significant effect on the work productivity of oil palm harvesting employees at PT. Betami Overseas Gardens.